Analisa Pemilihan Kursus Daring Pada Karyawan PT. Gramedia Asri Media dengan Metode Analytical Hierarchy Process - Jaelani, Ahmad; Purnamasari, Indah (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
PT. Gramedia Asri Media established the Gramedia Digital Technical Department which implements remote work so that it is possible for employees working in various places to stay connected and collaborate. However, with the limited space and time for employees and the difficulty of meeting at one time to get various trainings, then MOOC is expected to be the answer to the need for workers to get proper training and in accordance with the technical capabilities required by the company. MOOC (Massive Open Online Courses) is an example of technological development of the learning process that offers flexibility in time and place. Currently, there are many alternative MOOC providers with various criteria, so it is necessary to choose the one that is most suitable for its users. One method of making decisions based on many criteria is AHP (Analytical Hierarchy Process). This study uses 5 criteria, namely Teacher Credibility, Certificate, Price, Course Topics and Course Time and 4 alternatives, namely Coursera, EdX, Udemy and Codecademy, where the course topic is obtained as the priority with a priority weight of 0.2289 then followed by Course time with a priority weight of 0.2238 Price with priority weight 0.2133, Credibility of teachers with priority weight 0.1833, Certificate with priority weight 0.1508. While the alternative with the priority is Udemy with a priority weight of 0.4379 followed by Coursera with a priority weight of 0.2234, Codecademy with a priority weight of 0.1989 and lastly Edx with a priority weight of 0.1723.